Peran Political dan Military Connections Terhadap Pengungkapan Corporate Social Responsibility Perusahaan Pertambangan di Indonesia - Dwi Rahayu; Dian Nadia Novarina (AKUA: Jurnal Akuntansi dan Keuangan, 2024)
This study investigates whether political connections and military connections influence the level of Corporate Social Responsibility (CSR) disclosure in mining companies in Indonesia. The study employs a quantitative method with the population in mining sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The sample was selected using a purposive sampling method, totalling 102 samples from 34 mining sector companies listed on IDX for the 2019-2021 period. The data analysis techniques used panel data regression analysis with the EViews12 tools. The results show that political connections and military connections have a positive effect on CSR disclosure. Furthermore, this study used control variables, revealing that earnings management and financial performance don’t show a significant impact on CSR, while company size has a negative effect on CSR disclosure. The limitations of this study are associated with the sample size, which includes only mining companies in Indonesia and utilizes data from the past three years. During this period, the samples were under the influence of the COVID-19 pandemic. Therefore, for future study, it is necessary to expand the research time frame by involving a longer period. With an enhancement in CSR, it is also expected to contribute positively to financial performance. Keywords: Political Connection, Military Connection, Corporate Social Responsibility